The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4103/0970-9185.119148
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided quadratus lumborum block as a postoperative analgesic technique for laparotomy

Abstract: The quadratus lumborum (QL) block as a postoperative analgesic method following abdominal surgery has been described by Blanco for superficial surgeries but not used for major laparotomy. This ipsilateral QL block had low pain scores and opioid use on day one with sensory block upto T8-L1. The options of various volume used and pros and cons are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
105
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 6 publications
1
105
0
4
Order By: Relevance
“…4 In the past few years, several case reports have shown that the QLB has also been successful in providing postoperative pain relief. [5][6][7][8] In a previous randomized control study, we compared the QLB against a control group, in which we intentionally moved our point of injection from the original anterolateral side of the quadratus lumborum muscle to the posterior wall (QLB type 2). 9 This has become our standard practice, as we have abandoned the anterolateral approach completely subsequent to publication of our magnetic resonance study on optimal point of insertion and dispersion of local anesthetics.…”
mentioning
confidence: 99%
“…4 In the past few years, several case reports have shown that the QLB has also been successful in providing postoperative pain relief. [5][6][7][8] In a previous randomized control study, we compared the QLB against a control group, in which we intentionally moved our point of injection from the original anterolateral side of the quadratus lumborum muscle to the posterior wall (QLB type 2). 9 This has become our standard practice, as we have abandoned the anterolateral approach completely subsequent to publication of our magnetic resonance study on optimal point of insertion and dispersion of local anesthetics.…”
mentioning
confidence: 99%
“…The effective pain relief lasted for 12-14hours. Prolonged and continuous pain relief has been reported with catheter techniques for acute abdominal pain management [15] breast reconstruction [16] and laparotomy [11]. However, they all have used type-2 quadratus lumborum block.…”
Section: Discussionmentioning
confidence: 99%
“…Visoiu and Yakovleva [2] injected 10 mL LA between the anterior border of QL muscle and its fascia in a 5-year-old child for colostomy. Kadam [3] had similarly used anterior technique for QL block in an adult patient for laparotomy. In the anterior approach to QL block, probably LA spreads anteriorly towards transversus abdominis plane (TAP) as well as posteriorly towards paravertebral plane similar to posterior TAP block.…”
mentioning
confidence: 95%